2019
DOI: 10.3390/cancers11081076
|View full text |Cite
|
Sign up to set email alerts
|

PTEN Tumor-Suppressor: The Dam of Stemness in Cancer

Abstract: PTEN is one of the most frequently inactivated tumor suppressor genes in cancer. Loss or variation in PTEN gene/protein levels is commonly observed in a broad spectrum of human cancers, while germline PTEN mutations cause inherited syndromes that lead to increased risk of tumors. PTEN restrains tumorigenesis through different mechanisms ranging from phosphatase-dependent and independent activities, subcellular localization and protein interaction, modulating a broad array of cellular functions including growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
96
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(101 citation statements)
references
References 207 publications
(253 reference statements)
4
96
0
1
Order By: Relevance
“…The PI3K/AKT/mTOR signal transduction pathway is controlled by many factors. The tumour suppressor PTEN catalyses the reaction opposite of PIP3 generation by converting PIP3 to PIP2 [66,67]. PTEN downregulates the PI3K/AKT/mTOR pathway to suppress cell proliferation and interfere with cellular metabolism, and inhibition of PTEN activity activates AKT and downstream pathways [68].…”
Section: Ptenmentioning
confidence: 99%
“…The PI3K/AKT/mTOR signal transduction pathway is controlled by many factors. The tumour suppressor PTEN catalyses the reaction opposite of PIP3 generation by converting PIP3 to PIP2 [66,67]. PTEN downregulates the PI3K/AKT/mTOR pathway to suppress cell proliferation and interfere with cellular metabolism, and inhibition of PTEN activity activates AKT and downstream pathways [68].…”
Section: Ptenmentioning
confidence: 99%
“…The results of this present study showed genetic alterations in 7% of patients with metastatic breast cancer in the METABRIC study ( Figure 4B). This result is supported by a recent study which demonstrated that mutation in PTEN leads to inactivation of its function as tumor suppressor genes in cancer (Luongo et al, 2019). A recent review article discussed the possibility of PTEN as a potential biomarker of lymph node metastasis of esophageal squamous cell carcinoma (Li et al, 2019b).…”
Section: Analysis Of Genetic Alterations Of the Pbmentioning
confidence: 70%
“…In stem cells, the presence of p53 stops cell differentiation and promotes the conversion of stem cells to progenitor cells [111]. PTEN suppresses the PI3K/Akt pathway to inhibit cell differentiation and induce cell death [112]. RECK plays a role in tumor metastasis and angiogenesis by regulating MMPs.…”
Section: Mir-21mentioning
confidence: 99%